2023
DOI: 10.1002/inf2.12484
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance piezoresistive sensors based on transfer‐free large‐area PdSe2 films for human motion and health care monitoring

Rui Zhang,
Jie Lin,
Tao He
et al.

Abstract: Two‐dimensional transition metal dichalcogenides (TMDs) are needed in high‐performance piezoresistive sensors due to their strong strain‐induced bandgap modification and thereby large gauge factors. However, integrating a conventional high‐temperature chemical vapor deposition (CVD)‐grown TMD with a flexible substrate necessitates a transfer process that inevitably degrades the sensing properties of the TMDs and increases the overall fabrication complexity. We present a high‐performance piezoresistive strain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In Raman spectra (Figure 2a), the typical characteristic peaks centered on 512, 630 and 702 cm −1 in Com‐RuO 2 belong to the vibration modes E g , A 1g and B 2g respectively [10] . It is worth noting that after introducing abundant of GBs, the wave numbers of the three characteristic peaks of GB‐RuO 2 (501, 617, and 680 cm −1 ) decrease significantly compared with Com‐RuO 2 , which means that the vibration frequency of Ru−O is weakened and the spatial distance of Ru−O bond is lengthened [22–24] . This result is consistent with the XRD and HRTEM, which further proves that rich grain boundaries lead to surface tensile stress and provides a possibility for modulating RuO 2 ’s electronic structure.…”
Section: Resultsmentioning
confidence: 98%
“…In Raman spectra (Figure 2a), the typical characteristic peaks centered on 512, 630 and 702 cm −1 in Com‐RuO 2 belong to the vibration modes E g , A 1g and B 2g respectively [10] . It is worth noting that after introducing abundant of GBs, the wave numbers of the three characteristic peaks of GB‐RuO 2 (501, 617, and 680 cm −1 ) decrease significantly compared with Com‐RuO 2 , which means that the vibration frequency of Ru−O is weakened and the spatial distance of Ru−O bond is lengthened [22–24] . This result is consistent with the XRD and HRTEM, which further proves that rich grain boundaries lead to surface tensile stress and provides a possibility for modulating RuO 2 ’s electronic structure.…”
Section: Resultsmentioning
confidence: 98%
“…It is demonstrated that the first three vibration modes originate from the motion of Se atoms, and the A g 3 mode comes from the relative motion between Pd and Se atoms. 24 The XPS results are presented in Figure 1d,e.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…which is well compatible with the BEOL silicon circuit integration [24]. These achievements suggest that it is promising for strain sensors [25]. However, to the best of our knowledge, their pressure sensor that can be integrated into the MEMS platform has not yet been reported.…”
Section: Introductionmentioning
confidence: 81%
“…The Pd film was subsequently selenized by PES to obtain a polycrystalline PdSe 2 film at 200 °C. Notably, the low temperature is also compatible with widely used polyimide (PI) substrate, suggesting great potential for flexible devices [25]. Finally, the 5 nm Cr/50 nm Au electrodes were deposited by thermal evaporation.…”
Section: Device Design and Fabricationmentioning
confidence: 99%